Comparison of CRM Programs Basing on Improving Customer Profitability: Using the AHP Method - Xue, Dong-Fei; Zhao, Shi-Jie; Zhang, De-Peng (International Review of Management and Marketing, 2014)
In this paper, we generalize the cause-related marketing (CRM) methods that used by most current enterprises. And then, we probe into the difference of the effects of different types of CRM programs aiming at improving customer profitability by analytic hierarchy process (AHP). Consequently, we find out the sequencing results and provide some reference to the enterprises while performing CRM programs. Keywords: analytic hierarchy process; customer profitability; cause-related marketing JEL Classifications: M3